Rethinking health research capacity strengthening - Emily E. Vasquez; Jennifer S. Hirsch; Lê Minh Giang; Richard Parker (2013)
Health research capacity strengthening (HRCS) is a strategy implemented worldwide to improve the ability of developing countries to tackle the persistent and disproportionate burdens of disease they face. Drawing on a review of existing HRCS literature and our experiences over the course of an HRCS project in Vietnam, we summarise major challenges to the HRCS enterprise at the interpersonal, institutional and macro levels. While over the course of several decades of HRCS initiatives many of these challenges have been well documented, we highlight several considerations that remain underarticulated. We advance critical considerations of the HRCS enterprise by discussing (1) how the organisation of US public health funding shapes the ecology of knowledge production in low- and middle-income country contexts, (2) the barriers US researchers face to effectively collaborate in capacity strengthening for research-to-policy translation, and (3) the potential for unintentional negative consequences if HRCS efforts are not sufficiently reflexive about the limitations of dominant paradigms in public health research and intervention.